Three Bio-Realms : Biotechnology and the Governance of Food, Health, and Life in Canada - Doern, G. Bruce (Book collections on Project MUSE., 2012)
Three Bio-Realms provides the first integrated examination of the thirty-year story of the democratic governance of biotechnology in Canada.